A Study of Project-Based Learning with a Research-Based Approach: Improving Conceptual Understanding and Scientific Skills - Wirhanuddin,; Nadia,; Salsabila Dia Syahputri,; Kiki Putri Septya Pratama,; Zyahdatul Husna Herlianti, (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to analyze the effect of implementing the Project-Based Learning with a Research-Based Approach (PjBL-RBA) model in chemistry practicum on improving students’ conceptual understanding and scientific process skills. The research employed a quantitative approach with a one-group pretest–posttest design. The sample consisted of 26 undergraduate students from the Chemistry Education Study Program, Faculty of Teacher Training and Education, Mulawarman University, Indonesia, selected purposively to represent learners actively engaged in laboratory-based courses. Data collection instruments included a conceptual understanding test, an observation sheet for scientific process skills, and documentation of practicum activities. The data were analyzed using a paired sample t-test to determine statistical significance and N-Gain scores to measure the level of improvement. The results showed a significant enhancement in both variables with a p-value < 0.05. The average N-Gain scores of 0.53 for conceptual understanding and 0.38 for scientific process skills indicate a moderate level of improvement. The novelty of this study lies in the integration of Project-Based Learning with a Research-Based Approach in chemistry laboratory practice, which has rarely been explored simultaneously in previous literature. Therefore, the implementation of the PjBL-RBA model is proven effective and recommended as an innovative instructional strategy to strengthen students’ conceptual and scientific learning outcomes in higher education chemistry practicum.